Thinking Patterns in Decision-Making in Information Systems - Dragomir-Constantin, Florentina-Loredana (New Trends in Psychology, 2025)
The paper brings to the forefront the patterns of thinking used in national security information systems. The predictive models that underlie decision-making are presented and the psychological and technological vulnerabilities of cognitive biases are specified, as well as solutions for their correction. The improvement of national security by optimizing information systems with machine learning-based algorithms is emphasized.